Circulation of objects between strangers in public space: An analysis of forms of sociality among disposers and gleaners. (December 2016) - Roux, Dominique; Guillard, Valérie
The aim of this article is to understand how objects circulate between people who deposit them on the sidewalk (disposers), especially on "bulky item" collection (BIC) days and those who retrieve them (gleaners). Analysis of representations of 17 disposers and/or gleaners reveals three forms of sociality: (1) charitable donation (or disposing of items out of a wish to pass them on to other people), (2) balanced reciprocity (in which disposers and gleaners both view BIC as a system for the circulation of objects), and (3) generalized reciprocity (in which the desire to pool possessions is augmented by the wish to combat waste). The findings also reveal that the anonymity of the context leads disposers and gleaners to intersecting interpretations of what the other party is doing (for whom and why), which fuel and sometimes temper these forms of sociality. The findings add to the existing literature on disposition/gleaning by uncovering the forms of sociality at work between strangers in public space and the distinctive and anonymous circulation of objects resulting from them. The findings are also of relevance to public actors regarding the issues arising for waste management.